ANALISIS AGROINDUSTRI KERIPIK TEMPE BU SITI DI DESA BULUH RAMPAI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Nur Meganingsih; Evy Maharani; Shorea Khaswarina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study were to determine the amount of production costs, the added value and income of the entrepreneur crispy chips tempe Bu Siti in Buluh Rampai village, Seberida district Indragiri Hulu Regency. This research was conducted from April 2014 until July 2014. The data collection technique was case method to agroindustry entrepreneur of crispy chips Bu Siti in Buluh Rampai village. The analysis scopes of this research were costs, revenue, and added value analysis. The results of this research showed that at Mei 2014 the total cost crispy chips tempe was Rp. 27.544.183. Revenue to entrepreneur was Rp.36.064.161,50 and profit to entrepreneur was Rp.8.519.978,17. Profitability value meant that crispy chips tempe was a profitable industry because the value of profitability 1,31 Ratio of R/C value meant that every Rp.1,00 costs in the production process of crispy chips tempe will provide Rp.1,31 income. The added value of crispy chips tempe was Rp. 17.809,49/kg. Keywords: chrispy chips tempe, agroindustry, efficiency, added value